THE EFFECT OF FORMATIVE TEST RESULTS ON SUMMATIVE TEST RESULTS IN AL-QUR'AN HADITH SUBJECTS IN MAN TOMINI, PARIGI MOUTONG REGENCY - Nur Eka Wahyuningsih (Education Journal, 2021)
Based on field studies, the effect of formative test results and summative test results in Al-Qur'an Hadith subjects in MAN Tomini, Parigi Moutong Regency. The population in this study were all students of class XI MAN Tomini Parigi Moutong Regency, amounting to 154 students. The research sample was taken using proportional random sampling technique, the selected sample was 61 students. The instruments in this study use observation guidelines, interview guidelines, questionnaires or questionnaires and electronic recorders with data collection techniques through observation, interviews and documentation. The research data that has been collected is processed using the statistical product and service solution (SPSS) computer program and analyzed. using a simple linear regression formula. Research testing using normality test, linearity and hypothesis testing data. The results showed that there was a significant influence between the results of the formative tests and the results of the summative tests of Al-Qur'an subjects in class XI MAN Tominii, Parigi Moutong Regency. This can be seen from the t-count value of 5,785> t-table 2.001 so that is rejected and is accepted. And the coefficient of determination of this study shows the contribution of the influence of the independent variable (X), namely the formative test results on the dependent variable (Y), which is a result of 36.2% while the rest is influenced by other variables.